Ageing and mesenchymal stem cells derived exosomes: Molecular insight and challenges - Ahmadi, Mahdi; Rezaie, Jafar (Cell biochemistry and function, 2021)
Ageing induces a great risk factor that participates in progressing various degenerative diseases morbidities. The main characteristic of ageing is the failure in maintaining homeostasis in the organs with a cellular senescence. Senescence is characterized by reduced cell growth, evade cellular death, and acquiring a senescence‐associated secretory phenotype (SASP). Mesenchymal stem cells (MSCs) are advantageous cells in regenerative medicine, exerting pleiotropic functions by producing soluble factors, such as exosomes. MSCs and their exosomes (MSCs‐Exo) kinetic are affected by ageing and other aged exosomes. Exosomes biogenesis from aged MSCs is accelerated and their exosomal cargoes, such as miRNAs, vary as compared to those of normal cells. Besides, exosomes from aged MSCs loss their regenerative potential and may negatively influence the function of recipient cells. MSCs‐Exo can improve ageing and age‐related diseases; however, the detailed mechanisms remain yet elusive. Although exosomes‐therapy may serve as a new approach to combat ageing, the translation of preclinical results to clinic needs more extensive investigation on exosomes both on their biology and related techniques. Overall, scrutiny on the effect of ageing on MSCs and vice versa is vital for designing novel therapy using MSCs with focus on the management of older individuals.